2002
DOI: 10.1103/physrevlett.89.164502
|View full text |Cite
|
Sign up to set email alerts
|

Steep Sharp-Crested Gravity Waves on Deep Water

Abstract: A new type of steady steep two-dimensional irrotational symmetric periodic gravity waves on inviscid incompressible fluid of infinite depth is revealed. We demonstrate that these waves have sharper crests in comparison with the Stokes waves of the same wavelength and steepness. The speed of a fluid particle at the crest of new waves is greater than their phase speed. [5,6], requires knowledge of a form and dynamics of steep water waves. For the first time surface waves of finite amplitude were considered by S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 19 publications
5
23
0
Order By: Relevance
“…Nevertheless, the existence of a set of additional stagnation points, which approach the central stagnation point O as the steepness is increased, makes us expect that a 120 • singularity in the Stokes corner flow is indeed formed from several (probably an infinite number of) coalescing 90 • singularities supporting the conjecture of Grant (1973). Lukomsky et al (2002b) have numerically revealed a new type of flows, where fluid particles move faster than the wave itself in the vicinity of the wave crest due to the stagnation point located inside the flow domain. Because of this such flows and waves were called irregular.…”
Section: Stokes Flowsmentioning
confidence: 85%
See 2 more Smart Citations
“…Nevertheless, the existence of a set of additional stagnation points, which approach the central stagnation point O as the steepness is increased, makes us expect that a 120 • singularity in the Stokes corner flow is indeed formed from several (probably an infinite number of) coalescing 90 • singularities supporting the conjecture of Grant (1973). Lukomsky et al (2002b) have numerically revealed a new type of flows, where fluid particles move faster than the wave itself in the vicinity of the wave crest due to the stagnation point located inside the flow domain. Because of this such flows and waves were called irregular.…”
Section: Stokes Flowsmentioning
confidence: 85%
“…Note that the collocation method can be used instead but it is less efficient than expansion (18) (see Lukomsky et al, 2002b). The mean level η = η 0 should be zero for exact solutions.…”
Section: Nonlinear Transformation Of the Horizontal Scalementioning
confidence: 99%
See 1 more Smart Citation
“…A measure of this nonlinearity is that the maximum surface height is max = 0.175 which, for F L = 0.7, is roughly 71% of upper = F 2 L ∕2. While there has been extensive research devoted to studying the shape of a single highly nonlinear gravity wave, [25][26][27][28][29] it is particularly challenging to compute solutions to full free-surface flow problems (including the disturbance that causes the waves) with a train of waves with steepness of s > 0.1. Here, steepness is defined to be the wave amplitude divided by its wavelength.…”
Section: Flow Past a Pressure Distributionmentioning
confidence: 99%
“…Indeed, for an exact wave, the streamlines (in the frame of reference where the flow is steady) intersect at a right-angle above the crest, forming a stagnation point (Grant 1973;Longuet-Higgins & Fox 1977, 1978Lukomsky et al 2002b). The stagnation point approches the surface as ka increases.…”
Section: Wave Of Greatest Heightmentioning
confidence: 99%